Method for improving quality of cloth scraps through low-temperature shallow carbonization homogenization
By performing low-temperature shallow carbonization and grinding of cloth crushing, the problem that cloth crushing cannot be directly used as raw materials for fluidized bed boilers and airflow bed gasification furnaces is solved, and its Hastello abrasive index and heat value are improved, and the raw material requirements of the equipment are met.
Patent Information
- Application Number
- CN202411899538.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-08
AI Technical Summary
The existing cloth crushing cannot be used directly as raw materials for fluidized bed boilers and airflow bed gasifiers, and its Hastellometer wearability index is low, which cannot meet the raw material requirements of the equipment.
The cloth is homogenized and improved by low-temperature shallow carbonization technology. By pre-cutting and cutting the cloth, the width is reduced to less than 5cm, and carbonized under an inert atmosphere. The carbonization temperature is controlled at 247-257℃, with a time of 0.5-2 hours. Then grinding and screening are carried out to obtain powdered materials that meet the requirements.
The Hastello abrasiveness index of the cloth crushing is significantly improved, so that it is no less than 90%, reducing the energy consumption of the next step of crushing, and the heat value loss of the cloth crushing after treatment is controlled within 20%, and the heat value remains at 20~22MJ/kg, meeting the raw material requirements of the fluidized bed boiler or airflow bed gasifier.
Smart Images

Figure CN119771885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a renewable energy utilization technology for waste clothing, in particular to a method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization. Background Art
[0002] With the rapid development of urbanization in my country, the amount of urban domestic waste generated is increasing, and waste disposal has become a major environmental issue. Existing urban waste treatment technologies mainly include sanitary landfill, incineration, and composting. Although these methods can solve the waste disposal problem to a certain extent, they all have some shortcomings. For example, landfilling occupies a large amount of land and also produces leachate and methane, causing secondary pollution to the environment. Although incineration can effectively reduce the volume and amount of waste, it produces harmful substances such as dioxins, which have an impact on the environment and human health. Composting treatment has high investment costs, low fertilizer efficiency, and poses safety risks such as water and soil pollution. In recent years, people's understanding of existing domestic waste treatment technologies has gradually deepened. Landfill, composting, incineration, etc. alone can no longer meet the current demand for harmless treatment of huge amounts of domestic waste. The development of new and completely harmless domestic waste treatment technologies is urgent.
[0003] Take used clothing, for example. With growing environmental awareness, more and more residents are beginning to prioritize recycling. Instead of discarding their used clothing, they choose to put it in recycling bins or hand it over to professional recycling agencies. A nascent industrial chain has emerged for recycling used clothing, encompassing the production of recycled fibers and textile reprocessing. Some companies are beginning to enter the used clothing recycling sector, promoting its resourceful utilization. However, recycling used clothing requires certain technical and equipment support, and current technological and equipment limitations limit its efficiency.
[0004] Waste fabrics are typically composed of a variety of fibers, such as natural fibers (such as cotton and wool) and synthetic fibers (such as polyester and nylon). These fibers vary significantly in their physical and chemical properties and combustion characteristics, making it difficult to maintain a stable processing process. Different materials also vary significantly in toughness and strength, and the heterogeneity of fabric components makes it difficult to obtain uniformly sized materials. Currently, fabric scraps are primarily processed into fuel briquettes to provide heat for combustion furnaces in high-energy-consuming enterprises. This simple and crude method does not fully realize their potential. Some high-efficiency equipment, such as fluidized bed boilers and entrained-flow gasifiers, cannot utilize fuel briquettes. Furthermore, fabric scraps do not meet the feedstock fineness requirements of fluidized bed and entrained-flow equipment. Fluidized bed boilers primarily use fine coal within a certain particle size range as feedstock. Specific requirements include total moisture (Mt) and ash content (Ad) of no more than 40%, a GR.I ≤ 50, and a total sulfur (St,d) content generally less than 2.00%. Entrained-flow gasifiers typically use pulverized coal as a feedstock. Typically, the pulverized coal must pass through a 200-mesh sieve at least 70%, or have a particle size of less than 0.10 mm at least 85%. The ash content must be less than 25%, and the Hardgrove Grindability Index (HGI) must be greater than 40. However, the Hardgrove Grindability Index (HGI) of fabric chips is generally below 10, making them unsuitable for direct use as feedstock in fluidized-bed boilers and entrained-flow gasifiers. Summary of the Invention
[0005] The purpose of the present invention is to overcome the problem that existing cloth scraps cannot be used as raw materials for fluidized bed boilers and entrained flow gasifiers, and to provide a method for upgrading cloth scraps through low-temperature shallow carbonization and homogenization. After the cloth scraps are treated by this upgrading method, they are subjected to conventional grinding treatment to obtain ideal raw materials for fluidized bed boilers and entrained flow gasifiers, the particle size of which is less than 0.10 mm and has a high calorific value.
[0006] The Hardgrove grindability index of shredded cloth is low and cannot meet the raw material requirements of fluidized bed boilers and entrained flow gasifiers. The present invention uses low-temperature shallow carbonization to homogenize and improve the quality of the shredded cloth. Low-temperature shallow carbonization is a biomass pretreatment technology, currently mainly used in the quality pretreatment of biomass such as forest waste and straw. Low-temperature shallow carbonization can reduce the moisture content of the garbage, increase the fixed carbon content, and improve the calorific value of the raw material. The inventor believes that low-temperature shallow carbonization of shredded cloth can enhance the grindability and homogenization of the raw material, so that its Hardgrove grindability index (HGI) is not less than 90%, thereby greatly reducing the energy consumption of subsequent pulverization of the cloth. However, carbonization inevitably loses some of the calorific value of the shredded cloth. There is a contradiction between improving the Hardgrove grindability index and obtaining a high calorific value raw material. Therefore, how to make the Hardgrove grindability index (HGI) of the shredded cloth not less than 90% while controlling the calorific value loss of the shredded cloth to within 20% is the key problem to be solved by the present invention.
[0007] In order to solve the above problems, the present application first pre-cuts the cloth scraps and reduces their width to less than 5 cm to avoid the problem of local excessive carbonization caused by the difference in heat transfer during the carbonization process, improve the degree of homogenization, and avoid excessive loss of calorific value. Secondly, another key difficulty of the present invention is to determine the appropriate carbonization temperature and carbonization time. If the carbonization temperature is too low, the calorific value will increase less and the homogenization requirements will not be met; with the increase of the shallow carbonization temperature, the deoxidation capacity of the raw material increases and the calorific value is improved, but in order to obtain a higher Hardgrove grindability index, a higher shallow carbonization temperature is required, and a high carbonization temperature will lead to more mass and energy loss, which reduces the utilization rate of the raw material. The present application has obtained a suitable low-temperature shallow carbonization temperature through a combination of a large number of explorations and detection and analysis methods. While improving the grindability of the cloth scraps, the weight and calorific value of the cloth scraps are retained to the greatest extent, thereby ensuring the quality yield and energy efficiency of the product.
[0008] The specific plan is as follows:
[0009] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0010] S1. Cutting the scraps of cloth to obtain cut pieces with a width of less than 5 cm and a length of less than 50 cm;
[0011] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the temperature of the carbonization treatment is 247-257° C. and the time is 0.5 to 2 hours;
[0012] S3, grinding the carbonized material to obtain a powdery material;
[0013] S4. Send the powdered material to a screening device, and collect the undersize material as a raw material for a fluidized bed combustion device.
[0014] Furthermore, S1 also includes removing non-cloth impurities in the cloth scraps before the cutting process.
[0015] Furthermore, the cut material in S1 has a width of 1 to 4 cm and a length of 20 to 40 cm.
[0016] Furthermore, the cut material in S1 has a width of 2 to 3 cm and a length of 20 to 30 cm.
[0017] Furthermore, the temperature of the carbonization treatment in S2 is 250-255° C., and the time is 1 to 1.5 hours.
[0018] Furthermore, the grinding in S3 is performed using a grinding mill with a rotation speed of 100 to 300 rpm and a grinding time of 10 to 60 minutes.
[0019] Furthermore, the grinding in S3 is performed using a grinding mill with a rotation speed of 100 to 200 rpm and a grinding time of 10 to 30 minutes.
[0020] Furthermore, the pore size of the screening device in S4 is 0.05 to 0.1 mm.
[0021] Furthermore, the undersize material in S4 accounts for 85-100% of the total weight of the powdery material.
[0022] Furthermore, the material that does not pass through the screen in the screening device in S3 returns to step S3 to continue grinding.
[0023] Beneficial effects:
[0024] This application adopts the technology of low-temperature shallow carbonization, and the obtained cloth scraps have a Hardgrove grindability index of not less than 90, which is 9 to 10 times that of the original cloth scraps sample, greatly enhancing the grindability and homogenization degree of the raw materials, and greatly reducing the energy consumption and technical difficulty of the next step of crushing.
[0025] Furthermore, this application utilizes low-temperature, shallow carbonization technology, resulting in a weight loss rate of 12-15% for the shredded coal, which is considered normal and low. The calorific value of the treated shredded coal is 20-22 MJ / kg, approximately 90% of the calorific value of the raw material. This treatment maintains a high calorific value, maximizing the calorific value of the raw material while minimizing the mass loss. This allows the shredded coal to be used as a fly ash substitute for fluidized bed boilers or entrained flow gasifiers. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings. Obviously, the drawings described below only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0027] Figure 1 This is a photograph of a No. 1 cloth scrap sample provided in Example 1 of the present invention;
[0028] Figure 2 This is a photograph of a No. 2 cloth scrap sample provided in Example 1 of the present invention;
[0029] Figure 3 This is a thermogravimetric analysis diagram of cloth scrap sample No. 1 provided in Example 1 of the present invention;
[0030] Figure 4 This is a thermogravimetric analysis diagram of a No. 2 cloth scrap sample provided in Example 1 of the present invention;
[0031] Figure 5 This is an appearance diagram of a No. 1 cloth scrap sample provided in Example 1 of the present invention after carbonization at 240°C;
[0032] Figure 6 This is an appearance diagram of a No. 1 cloth scrap sample provided in Example 1 of the present invention after carbonization at 245°C;
[0033] Figure 7 This is an appearance diagram of a No. 1 cloth scrap sample provided in Example 1 of the present invention after carbonization at 250°C;
[0034] Figure 8 This is an appearance diagram of the No. 2 cloth scrap sample provided in Example 1 of the present invention after carbonization at 240°C;
[0035] Figure 9 This is a diagram showing the appearance of a No. 2 cloth scrap sample after carbonization at 245°C, provided in Example 1 of the present invention;
[0036] Figure 10 This is an appearance picture of the No. 2 cloth scrap sample provided in Example 1 of the present invention after carbonization at 250°C. DETAILED DESCRIPTION
[0037] The following are definitions of some terms used in the present invention. Other terms not mentioned here have definitions and meanings commonly known in the art:
[0038] Cloth scraps: Cloth scraps in the present invention refer to the cloth that is not used by the garment factory after the clothes are cut, the scraps in the cloth recycling, the tails and ends of cloth, and the cloth fragments generated in the recycling of waste clothes.
[0039] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, if specific techniques or conditions are not specified, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0040] The test methods used below include:
[0041] For the industrial analysis method of cloth scrap samples, please refer to the national standard GB / T 28731-2012 "Industrial Analysis Methods for Solid Biomass Fuels".
[0042] For the element content detection method of cloth scraps, please refer to the industry standard CJ / T 96-2013 "General Test Method for Chemical Properties of Domestic Waste".
[0043] Thermogravimetric analysis of the cloth scraps was performed using a thermogravimetric analyzer. The thermogravimetric analysis was conducted under continuous heating conditions. The gas atmosphere was air, the heating rate was 10°C / min, and the test temperature range was from room temperature to 350°C.
[0044] The Hardgrove Grindability Index (HGI) is tested using a Hardgrove Grindability Tester. The test method refers to the national standard GB / T 2565-2014 "Determination of Grindability Index of Coal".
[0045] Example 1
[0046] The two cloth scraps were analyzed for their physical and chemical properties. Sample 1 (see Figure 1 ) is mainly composed of broken cloth, a small amount of plastic and paper, and contains a small amount of dust. Sample No. 2 (see Figure 2 ) Mainly made of various cloth strips, with very little dust.
[0047] The industrial analysis of the cloth scrap samples is shown in Table 1.
[0048] Table 1 Industrial analysis of cloth scraps
[0049]
[0050] The elemental analysis results of the two cloth scrap raw material samples are shown in Table 2.
[0051] Table 2 Elemental analysis of cloth scraps (dry basis)
[0052]
[0053] Thermogravimetric analysis of two cloth scraps samples Figure 3 and Figure 4 Thermogravimetric analysis was performed under continuous temperature increase conditions, with air as the gas atmosphere, and the test temperature range was from room temperature to 350°C.
[0054] Sample No. 1 began to lose weight due to thermal volatilization at around 200°C. After 250°C, volatilization accelerated, causing the weight loss rate to increase, until an inflection point appeared at around 330°C, and the weight loss rate began to decrease. When the temperature rose to 350°C, the sample lost 27.51% of its weight. Sample No. 2 showed obvious volatilization at around 230°C, and began to volatilize rapidly at around 275°C, and the volatilization slowed down significantly at around 310°C. At 350°C, the sample had only lost 11.06% of its weight. Overall, the processing temperature required for Sample 2 should be higher than that of Sample 1, but the total weight loss of Sample 2 during the heat treatment process was significantly lower than that of Sample 1.
[0055] The calorific value analysis results for the cloth scrap samples are shown in Table 3 below. The samples exhibit relatively high calorific values, with Sample 1 having a high calorific value of approximately 22.2 MJ / kg and Sample 2 having a high calorific value of 24.1 MJ / kg. Sample 2, being pure cloth scraps, has a higher calorific value than Sample 1. Using the calorific values of coal and biomass as a reference, the calorific value of standard coal is 29.3 MJ / kg; the calorific value of biomass ranges from 13 to 22 MJ / kg. The calorific value of the cloth scrap samples is approximately 35% higher than the generally accepted average calorific value of biomass.
[0056] Table 3 Calorific value analysis of cloth scraps
[0057]
[0058] Low-temperature shallow carbonization treatment is carried out in an inert atmosphere (such as nitrogen) using a tubular heating furnace, and the carbonization time is set to 1 hour. Based on the results of thermogravimetric analysis, the low-temperature shallow carbonization temperature starts from 200°C and goes up to 280°C, with a temperature interval of 10°C. After finding the critical treatment temperature range, the temperature interval is set at 5°C.
[0059] Experiments have shown that when samples are treated at temperatures between 200°C and 230°C, the appearance of the fabric shreds changes minimally, and initial shreds demonstrate strong toughness. Therefore, temperatures below 230°C are insufficient for achieving reasonable grindability through low-temperature, shallow carbonization of the fabric shreds. At shallow carbonization temperatures above 260°C, the shreds turn almost completely black. Therefore, the ideal temperature range for low-temperature, shallow carbonization should be between 240°C and 260°C.
[0060] After the two samples were further treated at a temperature interval of 5°C, the appearance of the samples was as follows: Figure 5-10 shown.
[0061] from Figure 5-10 It can be seen that after carbonization at 240°C, the overall color of the cloth began to deepen. As the temperature increased, the black area increased and the color deepened more obviously.
[0062] During the low-temperature shallow carbonization process, the fibers of the sample are thermally damaged and broken, and some volatile substances are also lost. In principle, it is hoped that low-temperature shallow carbonization can achieve an increase in the grindability index while minimizing the weight loss of the sample.
[0063] The weight loss of the cloth scraps after low-temperature shallow carbonization is shown in Table 4. As the temperature increased, the weight loss of the samples increased, with Sample 2 showing better overall weight loss than Sample 1. Sample 1, composed of cloth scraps and small amounts of waste paper and plastic, was optimally treated at a low-temperature shallow carbonization temperature between 245°C and 250°C. The optimal low-temperature shallow carbonization temperature for Sample 2 was 255°C. At the optimal treatment temperature, Sample 1 lost approximately 15% of its weight, while Sample 2 lost approximately 12%. Compared to biomass, this weight loss is within a reasonable and relatively low range.
[0064] Table 4 Weight loss rate of cloth scraps after low temperature shallow carbonization
[0065]
[0066]
[0067] The elemental analysis of the materials at different low-temperature shallow carbonization treatment temperatures is shown in Table 5 below. Overall, compared with the original cloth pieces, the carbon content is generally increased after low-temperature shallow carbonization.
[0068] Table 5 Elemental analysis of samples after low temperature shallow carbonization
[0069]
[0070] Table 6 shows the volatile matter and calorific value of the raw materials after low-temperature shallow carbonization at various temperatures near the optimal treatment temperature. The calorific value of the raw materials after low-temperature shallow carbonization decreased slightly compared to the pre-treatment value. This is due to the volatilization of light components, which typically have a relatively high calorific value. This results in a slight decrease in calorific value per unit weight, but the decrease is not significant. At the optimal treatment temperature, the calorific value loss per unit weight of sample No. 1 is approximately 10%, and that of sample No. 2 is approximately 11.5%. The calorific value of the cloth scraps after low-temperature shallow carbonization is approximately 20-22 MJ / kg, approximately 90% of the calorific value of the raw materials. The calorific value of the treated samples remains high.
[0071] Table 6 Volatile matter and calorific value of cloth scraps after low-temperature shallow carbonization
[0072]
[0073]
[0074] Table 7 shows the grindability index of samples after low-temperature shallow carbonization at different temperatures. The Hardgrove Grindability Index (HGI) is an important parameter that measures the ease with which a solid can be ground into powder and is used to evaluate mill energy consumption. A higher HGI indicates a more grindable material. The grindability index of the shredded sample is highly sensitive to processing temperature; a temperature increase of just 5°C can significantly affect the index.
[0075] Table 7 Grindability index of cloth scraps after shallow carbonization treatment
[0076]
[0077] The photo of sample No. 1 in this example after carbonization at 240°C is shown in Figure 5 After carbonization, the grindability index is poor, only 16, which is not significantly increased compared to the original cloth fragments, resulting in it being unable to be ground to produce powdered materials. Under 245℃, 1h treatment, the cloth fragment morphology of sample No. 1 is shown. Figure 6 The color is obviously deepened, but the grindability index still cannot meet the requirements. When the shallow carbonization temperature of sample No. 1 is controlled at 250℃ and other technical parameters are the same, the appearance after shallow carbonization is shown in Figure 2. Figure 7 , its color is darker than Figure 6Deeper. Sample No. 1 had a unit mass loss of 16.1%, which is within a reasonable range compared to biomass. After shallow carbonization, its calorific value reached 19,899.63 kJ / kg, remaining high compared to the raw material. The Hardgrove Grindability Index of the sample carbonized at 250°C reached 95, making it suitable for use as a feedstock in fluidized bed boilers or entrained flow gasifiers. Compared to 245°C, a temperature of just 5°C significantly impacted the grindability index, demonstrating that the grindability index of this sample is highly sensitive to treatment temperature.
[0078] Since sample No. 2 is pure cloth, its calorific value is higher than that of sample No. 1. After treatment at 245℃ for 1h, sample No. 2 Figure 8 , the carbon content has increased compared with the original cloth scraps. After treatment at 245℃ for 1h, the unit mass loss of the cloth scraps of sample No. 2 is only about 5%; the calorific value of the cloth scraps after low-temperature shallow carbonization is about 21-22MJ / kg, which exceeds 90% of the original calorific value, and the calorific value of the treated sample remains at a high level. However, the Hardgrove grindability index of the cloth scraps of sample No. 2 after carbonization treatment at 245℃ is only 14, which does not meet the requirements of fluidized bed combustion materials. When the carbonization temperature is controlled at 250℃, the other technical parameters are the same. The appearance after shallow carbonization can be seen Figure 8 , the unit mass loss of the sample is 11.1%, and the mass loss is in a reasonable to low range. After shallow carbonization, its calorific value is 21571.04kJ / kg, and compared with the raw material, the energy loss is low. After the sample is carbonized at 250℃, the Hardgrove index of the cloth is 48, and the grindability is not high. At this temperature, although the shallow carbonization treatment preserves the quality and calorific value of the raw materials, it cannot meet the homogenization requirements for the cloth. When the shallow carbonization temperature of sample No. 2 is controlled at 255℃, and other technical parameters are the same, the appearance after shallow carbonization is shown. Figure 9 , the color is darker than 250℃. As the temperature rises, the degree of carbonization also deepens. Its unit mass loss is 12.0%, and the mass loss is in a reasonable and low range. Its calorific value after shallow carbonization is 21319.36kJ / kg. Compared with the raw material, the energy loss is low. 2 Good samples have a Hardgrove index of up to 94 after carbonization at 255℃. It can be inferred that the optimal shallow carbonization temperature of this cloth scrap sample is around 255℃. In general, when the heat treatment temperature is low, the grindability index of the cloth scrap sample is relatively low. Conversely, if the cloth scraps are not heated and baked, their grindability index will be even worse. Therefore, it is not suitable to directly grind the raw materials to obtain powdered materials.
[0079] Example 2
[0080] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0081] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0082] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 247° C. and the time is 1.5 hours;
[0083] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0084] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 21645.23 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0085] The material that passes through the screen accounts for 88% of the total weight of the powdered material, and the material that does not pass through the screen is returned to step S3 for further grinding.
[0086] Example 3
[0087] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0088] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0089] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization temperature is 250° C. and the time is 1.5 hours;
[0090] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0091] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 21402.36 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0092] The material that passes through the screen accounts for 90% of the total weight of the powdered material, and the material that does not pass through is returned to step S3 for further grinding.
[0093] Example 4
[0094] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0095] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0096] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 255° C. and the time is 1.5 hours;
[0097] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0098] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 20258.06 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0099] The material that passes through the screen accounts for 92% of the total weight of the powdered material, and the material that does not pass through the screen is returned to step S3 for further grinding.
[0100] Example 5
[0101] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0102] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0103] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 257° C. and the time is 1.5 hours;
[0104] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0105] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 20179.07 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0106] The material that passes through the screen accounts for 95% of the total weight of the powdered material, and the material that does not pass through the screen is returned to step S3 for further grinding.
[0107] Example 6
[0108] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0109] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 40 cm;
[0110] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 255° C. and the time is 0.5 h;
[0111] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0112] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 21532.51 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0113] The material that passes through the screen accounts for 90% of the total weight of the powdered material, and the material that does not pass through is returned to step S3 for further grinding.
[0114] Example 7
[0115] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0116] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0117] S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 255° C. and the time is 1.5 hours;
[0118] S3, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 30 minutes to obtain a powdery material;
[0119] S4. The powdered material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 20256.15 kJ / kg, which meets the raw material requirements of the fluidized bed combustion device.
[0120] The material that passes through the screen accounts for 95% of the total weight of the powdered material, and the material that does not pass through the screen is returned to step S3 for further grinding.
[0121] Comparative Example 1
[0122] Referring to Example 3, except that step S1 is not performed, the process is as follows:
[0123] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0124] S1, placing the cloth pieces in an inert atmosphere for carbonization treatment, wherein the carbonization treatment temperature is 250° C. and the time is 1.5 hours;
[0125] S2, grinding the carbonized material using a grinding mill at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0126] S3. The powdery material is fed into a screening device with a sieve aperture of 0.1 mm. The material under the sieve is collected as a raw material for a fluidized bed combustion device. The calorific value thereof is 19683.56 kJ / kg, which basically meets the raw material requirements of the fluidized bed combustion device.
[0127] The material that does not pass through the screen accounts for 84% of the total weight of the powdered material, and the process returns to step S2 to continue grinding.
[0128] Comparative Example 2
[0129] Referring to Example 3, except that step S2 is not performed, the process is as follows:
[0130] A method for improving the quality of cloth scraps through low-temperature shallow carbonization and homogenization, comprising the following steps:
[0131] S1. removing impurities such as stones and plastic from the cloth scraps, and then cutting the cloth scraps to obtain cuttings with a width of 2 cm and a length of 20 cm;
[0132] S2, grinding the cut material, using a grinding mill, grinding at a speed of 200 rpm for 10 minutes to obtain a powdery material;
[0133] S3. The powdery material is sent to a screening device. The aperture of the screen is 0.1 mm. The powdery material cannot pass through the screen and the screened material cannot be collected.
[0134] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the scope of protection of the present invention.
[0135] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0136] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization, characterized in that: The following steps are involved: S1, cutting the cloth scraps to obtain cutting materials with a width of less than 5 cm and a length of less than 50 cm; S2, placing the cut material in an inert atmosphere for carbonization treatment, wherein the temperature of the carbonization treatment is 247-257° C. and the time is 0.5 to 2 hours; S3, grinding the carbonized material to obtain a powdery material; S4, sending the powdery material to a screening device, and collecting the screened material as a raw material for a fluidized bed combustion device.
2. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 1, characterized in that: S1 also includes removing non-cloth impurities in the cloth scraps before the cutting process.
3. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 2, characterized in that: The cut material in S1 has a width of 1 to 4 cm and a length of 20 to 40 cm.
4. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 3, characterized in that: The cut material in S1 has a width of 2 to 3 cm and a length of 20 to 30 cm.
5. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to any one of claims 1 to 4, characterized in that: The temperature of the carbonization treatment in S2 is 250-255° C., and the time is 1 to 1.5 hours.
6. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to any one of claims 1 to 4, characterized in that: The grinding in S3 is performed by a grinding machine with a rotation speed of 100 to 300 rpm and a grinding time of 10 to 60 minutes.
7. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 6, characterized in that: The grinding in S3 is performed by a grinding machine with a rotation speed of 100 to 200 rpm and a grinding time of 10 to 30 minutes.
8. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to any one of claims 1 to 4, characterized in that: The aperture of the screening device in S4 is 0.05-0.1 mm.
9. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 8, characterized in that: The undersize material in S4 accounts for 85-100% of the total weight of the powdery material.
10. The method for improving the quality of cloth scraps by low-temperature shallow carbonization homogenization according to claim 9, characterized in that: The material that has not passed through the screen in the screening device in S3 returns to step S3 to continue grinding.
Citation Information
Patent Citations
Method for producing active carbon by using traditional Chinese medicine dregs
CN101544370A
Method for production of carbonized cloth, and carbonized cloth produced thereby
CN101578405A
High-first-effect high-specific-volume biomass hard carbon, acid pretreatment preparation method thereof and sodium ion battery
CN118183705A
Method for producing nonwoven fabric-like active carbon and nonwoven fabric-like active carbon
JP2004183115A
Processing method for discarded cloth product and processing device for discarded cloth product
WO2023209890A1